2023
DOI: 10.1002/ajhb.23952
|View full text |Cite
|
Sign up to set email alerts
|

Early life predictors of body composition trajectories from adolescence to mid‐adulthood

Abstract: ObjectivesGuatemala has experienced rapid increases in adult obesity. We characterized body composition trajectories from adolescence to mid‐adulthood and determined the predictive role of parental characteristics, early life factors, and a nutrition intervention.MethodsOne thousand three hundred and sixty‐four individuals who participated as children in a nutrition trial (1969–1977) were followed prospectively. Body composition characterized as body mass index (BMI), fat mass index (FMI), and fat‐free mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…LBW is frequently associated with maternal malnutrition, smoking, stress, and inadequate antenatal care (Khan et al, 2020). Focusing on life-course plasticity, a large number of studies have shown that the birth weight and the low level of nutritional intake in early life followed by alterations in growth trajectory and metabolism, may impact subsequent obesity risk (Kuzawa et al, 2012;Poveda et al, 2023;Wang et al, 2018). This phenomenon can be understood in terms of developmental plasticity and DOHaD concept (Kuzawa & Pike, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LBW is frequently associated with maternal malnutrition, smoking, stress, and inadequate antenatal care (Khan et al, 2020). Focusing on life-course plasticity, a large number of studies have shown that the birth weight and the low level of nutritional intake in early life followed by alterations in growth trajectory and metabolism, may impact subsequent obesity risk (Kuzawa et al, 2012;Poveda et al, 2023;Wang et al, 2018). This phenomenon can be understood in terms of developmental plasticity and DOHaD concept (Kuzawa & Pike, 2005).…”
mentioning
confidence: 99%
“…In the capital Maputo, the high rate of infant mortality (63.9 per thousand) is concentrated within the neonatal period because of the prevalence of LBW and small for gestational age (SGA) (Garcia-Basteiro et al, 2017). LBW children who survive are more likely to suffer stunted growth during infancy and into adulthood, increasing the risk of obesity and diabetes (de Souza et al, 2022;Gima & Nakamura, 2022;Poveda et al, 2023). Furthermore, previous studies in Maputo have shown that LBW children were lighter and smaller than normal birthweight children and presented deficits in neuromotor development and physical fitness (dos Santos et al, 2014;Tchamo et al, 2017).…”
mentioning
confidence: 99%